Efektivitas Gel Daun Sirih Merah pada Percepatan Penyembuhan Luka Perineum pada Ibu Post Partum - Chyntia Haryana; Suharyo Hadisaputro; Arwani Arwani (Universitas Malahayati, 2026)
ABSTRACT According to the World Health Organization (WHO), perineal wounds in childbirth affect 2.7 million cases worldwide, a number projected to rise to 6.3 million by 2050. In Indonesia, 75% of mothers who give birth vaginally experience perineal rupture. Among 1,951 spontaneous births, 57% of mothers require perineal sutures due to episiotomy or spontaneous tears. The healing of perineal wounds can be supported by non-pharmacological therapies, one of which is the use of red betel leaf gel. The purpose of this research was to prove the effect of red betel leaf gel on perineal wound healing in postpartum mothers. This study employed a quasi-experimental design with a pretest-posttest nonequivalent groups design. The sample consisted of 30 postpartum mothers with second-degree perineal wounds, selected through simple random sampling. The participants were divided into two groups: an intervention group received red betel leaf gel treatment and a control group treated with 10% Povidone-Iodine. Perineal wound healing in postpartum mothers was assessed using the REEDA score. The statistical test used in this study is the Mann-Whitney test. Giving red betel leaf gel has an effect on perineal wound healing in postpartum mothers. There is a difference in REEDA scores between the administration of red betel leaf gel compared to Povidone Iodine 10% treatment with p-value 0,000. Red betel leaf gel has an effect on perineal wound healing in postpartum women. It is suggested that postpartum mothers should use red betel leaf gel regularly according to the recommended dose. Keywords: Perineal Wound, Post Partum Mothers, Red Betel Leaf Gel. ABSTRAK Luka perineum pada ibu bersalin menurut World Health Organization (WHO) terdapat 2,7 juta kasus yang diperkirakan akan meningkat menjadi 6,3 juta pada tahun 2050. Di Indonesia, 75% ibu melahirkan pervaginam mengalami rupturperineum, dan dari 1951 kelahiran spontan, 57% ibu memerlukan jahitan perineum akibat episiotomi robekan spontan. Penyembuhan luka perineum dapat menggunakan terapi non farmakologis salah satunya yaitu penggunaan gel daun sirih merah. Tujuan penelitian ini adalah untuk membuktikan pemberian gel daun sirih merah berpengaruh terhadap penyembuhan luka perineum pada ibu post partum. Jenis penelitian ini adalah quasy experiment design dengan rancangan pretest-posttest nonequivalent groups design. Jumlah sampel penelitian 30 responden ibu post-partum dengan luka perineum derajat II yang dipilih secara acak sederhana, dibagi menjadi kelompok intervensi yang diberikanperlakuan berupa gel daun sirih merah, dan kelompok kontrol diberikan Povidone Iodine 10%. Penyembuhan luka perineum pada ibu post partum diukur menggunakan skor REEDA. Uji statistik yang digunanakan adalah Mann-Whiney. Pemberian gel daun sirih merah berpengaruh terhadap penyembuhan luka perineum pada ibu post partum. Adaperbedaan skor REEDA antara pemberian gel daun sirih merah dibandingkan dengan perawatan Povidone Iodine 10% dengan nilai p-value sebesar 0,000. Pemberian gel daun sirih merah berpengaruh terhadap penyembuhan luka perineum pada ibu post partum. Disarankan ibu post partum menggunakan gel daun sirih merah secara rutin sesuai dosis yang direkomendasikan. Kata Kunci: Luka Perineum, Ibu Post Partum, Gel Daun Sirih Merah.